Intersexual stages. Ambiguous genitals. - Salvador G. Carrillo Soriano (Medisur)
It is considered that every newborn that presents a confused aspect of external genitalia, that does not permit to define his phenotypic sex, has Ambiguous Genitals. It includes real cases of intersex abnormalities, or those with severe hypospadia and bilateral chryptorchidism. In spite of the large advances in genetic, hormonal regulation and molecular biology studies in intersex abnormalities, today continues being motive of confussion when a doctor found a newborn with ambiguous genitalia. We presented the Good Clinical Practices Guideline for Intersex and ambiguos genitalia, approved by consensus in the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba, March, 2005).